Synthesis of histamine by Haemophilus influenzae. - Sheinman, B D (1986)
Recent findings suggest that bacteria might contribute to histamine concentrations in the sputum of patients with infective lung disease. Ten isolates of Haemophilus influenzae from patients with acute exacerbation of chronic bronchitis and emphysema, together with two reference strains, were incubated at 37 degrees C for 72 hours. Serial estimations of histamine concentrations by high pressure liquid chromatography showed significant increases at 24 and 48 hours; no increases were evident in the control samples. These findings suggest that H influenzae might contribute to inflammation and limited airflow in infective lung disease by producing histamine.